Prospect of the Young Generation in Halal and Sharia Demand - Wiwiet Prihatmadji; Taufan Maulamin; Noviandari Sari Utami (ASIAN PUBLISHER, 2025)
This journal article explores the burgeoning demand for halal products and Sharia-compliant services among the young generation, specifically Millennials and Gen Z. Drawing upon recent surveys and industry reports, it highlights the ethical and digital drivers behind this trend, analyzes the current market landscape, identifies key barriers to adoption, and outlines significant opportunities. The paper argues that as this demographic increasingly seeks alignment between their values and consumption habits, the halal and Sharia sectors are poised for substantial growth, necessitating strategic adaptation and innovation from industry players.